The priesthood of science : a work of Utopian fiction - Leiss, William, 1939- (Leiss, William, 1939- Herasaga, 2008)
The global political situation is increasingly volatile, and Hera and her sisters are sealed off from the rest of the world in southern Nevada. She is still tormented by her parents' decision to genetically modify the brains of their twelve daughters--and by her own agreement to allow a similar procedure to be used on a much larger group of human embryos. That group of engineered embryos has become one thousand young people just turning eighteen, and the gender politics among them is threatening to ruin Hera's gamble on a new beginning for human society. The Priesthood of Science envisions a fu.